Specific Characteristics of Business Negotiation in the SEE Trading Companies - Maric, Radenko M; Janać, Jan (Industrija, 2014)
The aim of this paper is to determine, based on empirical research, whether there is a statistically significant correlation between the cultural, economic and political factors, and business negotiation in the trade sector of selected countries in the South-Eastern Europe (SEE): Serbia, Croatia, Bosnia and Herzegovina, Hungary and Montenegro. Data on the research problem are collected electronically through questionnaires, while obtained results are interpreted by using parametric statistical tests: a two-way Analysis of Variance (ANOVA) test and the Least Significant Difference (LSD) test. After obtained results are analyzed, the empirical research has shown that there is a significant correlation between the aforementioned factors and business negotiation, which served as a basis for creating the profile of a business negotiator in regional trade companies. The research results provide the grounds for future researches that should examine the impact of sub-groups within the analyzed factors on the success of business negotiation.
Keywords: Business negotiations; Trade; Trade companies; Human resources